Influence of different corrosion environments on mechanical properties of a roadbed rehabilitation polyurethane grouting material under uniaxial compression. (27th September 2021) - Wang, Zhenyang; Du, Mingrui; Fang, Hongyuan; Zhang, Chao; Li, Manjun; Shi, Mingsheng
Highlights: The variations of mass and P-wave velocity of PU grouting materials after chemical corrosion were studied. The influences of different corrosive environments on the mechanical properties of PU grouting materials were analyzed. The damage factor of the PU grouting materials was defined based on the variations of their P-wave velocity. The statistical damage constitutive model of PU under the coupling effect of corrosion and load was established. Abstract: The mechanical properties of the roadbed rehabilitation polyurethane (PU) grouting materials subjected to different chemical corrosion are the theoretical basis for evaluating the long-term performance, which, however, is not clear yet. Here, the PU grouting materials with different densities were immersed in water, H2 SO4, HCl, and NaOH solutions for different times, followed by the P-wave velocity tests and uniaxial compression tests. The influences of different corrosion environments on the damage and uniaxial compressive strength of PU samples were analyzed, and the statistical damage constitutive model under the coupling effects of chemical corrosion and the external load was established. Results show that the water brings little influence whereas both the acid and alkaline environments degrade the strength of PU grouting materials, and the longer the chemical corrosion time is, the greater the decrease in strength. The maximum declines in the yield strength of PU samples corroded by H2 SO4, HCl, and NaOH solutions are about 32.8%, 31.3%, and 21.4%, respectively. The theoretical stress–strain curves based on the statistical damage constitutive model are in agreement with the experimental ones before yielding (with the average difference of 0.077–1.017 MPa), indicating the rationality of the theoretical model.